Destrutturare l'aula, ma con metodo: spazi e orizzonti epistemologici per una didattica aumentata dalle tecnologie - Paolo Ferri; Stefano Moriggi (LED Edizioni Universitarie, 2016)
This first paragraphs of this paper has been developed into two levels of argumentation. The first aimed to perform a genealogical analysis of the role of the different technologies (book and digital media) in redefine time, spaces, methods and relationships within the learning environments. More in detail we try: (a) to define the relationship between evolution of educational technologies and the new growing strategies for learning and teaching; (b) to understand the close connection (cultural and practical) among digital media, new teaching methods (based on the constructivist paradigm) and different educational environments and settings. As a consequence, the paper sketches an analysis of the «new» digitally augmented spaces for learning. In particular, we point out how methodological and didactical innovation and design of new «spaces and multiple environments» for learning are inextricably linked. They are actually the spaces in which it possile to apply new technologies for augmented learning. From all these points of view, the traditional classroom is definitely obsolete.